1997
DOI: 10.1002/(sici)1096-8628(19970502)70:1<87::aid-ajmg16>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Partial trisomy 17q22-qter and partial monosomy Xq27-qter in a girl with a de novo unbalanced translocation due to a postzygotic error: Case report and review of the literature on partial trisomy 17qter

Abstract: Partial trisomy 17q22-qter is a rare but well-recognized clinical entity. We present a case of partial trisomy for the long arm of chromosome 17, which was detected in a female infant with severe psychomotor and somatic retardation, Stargardt disease, short limbs, and numerous minor anomalies. Differential chromosomal staining demonstrated an excess of genetic material on the long arm of the late replicating X chromosome. FISH and DNA polymorphism analysis showed that the extra material belonged to the distal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…The etiology of trisomy 8 therefore seems to differ from that of common autosomal trisomies, even when considering only liveborn mosaic cases, 13,14 and represents a new addition to the expanding category of mitotically derived chromosome abnormalities, as previously described in some cases of homologous Robertsonian translocations and isochromosomes 40,41 and unbalanced de novo translocations. 42,43 An excess of males was observed in the present study (19M:7F) as previously reported from clinical series. 16,20 Looking only at the mitotic cases in our study, the skewed sex ratio persists (15M:5F).…”
Section: Discussionsupporting
confidence: 90%
“…The etiology of trisomy 8 therefore seems to differ from that of common autosomal trisomies, even when considering only liveborn mosaic cases, 13,14 and represents a new addition to the expanding category of mitotically derived chromosome abnormalities, as previously described in some cases of homologous Robertsonian translocations and isochromosomes 40,41 and unbalanced de novo translocations. 42,43 An excess of males was observed in the present study (19M:7F) as previously reported from clinical series. 16,20 Looking only at the mitotic cases in our study, the skewed sex ratio persists (15M:5F).…”
Section: Discussionsupporting
confidence: 90%
“…Hypertrichosis had previously been reported in a case of partial trisomy 17q22-qter associated with a de novo unbalanced translocation [14], suggesting that the distal portion of human chromosome 17q may contain dosage-sensitive genes that contribute to excessive hair growth. Recently, a series of microdeletions were reported on chromosome 17q24.2–q24.3 in three cases of familial congenital generalized hypertrichosis terminalis with gingival hyperplasia (CGHT), as well as a de novo microduplication within this same region in a case of sporadic CGHT [15].…”
Section: Introductionmentioning
confidence: 88%
“…Partial trisomy 17q releated to recognizable dysmorphic evidences and psychomotor retardation. 6 Mental and growth retardation, microcephaly, high forehead, frontal bossing, temporal retraction, short and broad nose, broad and flat nasal bridge, large mouth with down-turned corners, thin upper lip, cleft palate, low-set and malformed ears, short and webbed neck, limb shortness and skeletal anomalies, abnormalities of genital, brain, heart and kidney were reported in partial trisomy17q patients. 6,7 Cordier et al first reported a combination of partial trisomy 17q and monosomy 5p in fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, 32 cases of partial trisomy for the distal region of 17q were reported either inherited or de novo. [2][3][4][5][6][7][8] A derivative chromosome 4 due to partial trisomy of chromosome 17q has never been described, to our knowledge. We demonstrated that the fetus was a carrier of a de novo derivative chromosome 4 arising from partial trisomy 17q.…”
mentioning
confidence: 99%